1984
DOI: 10.1007/bf01309305
|View full text |Cite
|
Sign up to set email alerts
|

Verapamil inhibits influenza A virus replication

Abstract: Calcium channel blockers reduce Ca++ flux through membrane channels and may inhibit intracellular Ca++-dependent synthetic and regulatory activities by binding to calmodulin. We have found that Verapamil, a calcium channel blocker, inhibits influenza virus replication in Madin-Darby canine kidney cells and in murine pulmonary macrophages and that this antiviral effect occurs with drug addition late in the replication cycle. Chlorpromazine, a drug which binds to calmodulin, also inhibited influenza virus replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 8 publications
6
36
0
1
Order By: Relevance
“…Other investigators have also demonstrated an inhibitory effect of Verapamil on replication of human cytomegalovirus (Albrecht et al, 1984), Epstein-Barr virus (Nemerov & Cooper, 1984) and influenza virus (Nugent & Shanley, 1984). Taken together, these results clearly demonstrate that Verapamil exhibits anti-viral and anti-chlamydia1 activity in uitro.…”
Section: Discussionsupporting
confidence: 66%
“…Other investigators have also demonstrated an inhibitory effect of Verapamil on replication of human cytomegalovirus (Albrecht et al, 1984), Epstein-Barr virus (Nemerov & Cooper, 1984) and influenza virus (Nugent & Shanley, 1984). Taken together, these results clearly demonstrate that Verapamil exhibits anti-viral and anti-chlamydia1 activity in uitro.…”
Section: Discussionsupporting
confidence: 66%
“…Beside its calcium channel blocking activity, Verapamil also affects PKC activation [14]. In IV-infected cells, the PKC inhibition impairs ERK-activation [12], which is essential for efficient nuclear RNP export at the late stage (6-10 h p.i.)…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1A) is long known to reduce influenza virus replication [14]. In order to analyse this antiviral effect in more detail, we first defined the cytotoxic concentration of Verapamil at which 50% of A549 cells (as an example for human alveolar epithelia cells) are still viable (CC 50 ).…”
Section: Verapamil Efficiently Reduces Influenza a And B Virus (Iav Amentioning
confidence: 99%
See 2 more Smart Citations